A framework for an action plan to implement health and family life education in schools - Wiltshire, Annette (UNICEF, 1996)
This framework was produced as a tool for designing and developing the processes necessary for the formulation and implementation of health and family life education (HFLE) in the education systems of CARICOM Member States. As such, it is intended to guide or enhance the development of national action plans that reflect the unique resources, needs, priorities, and aspirations, as well as religious, cultural, and socio-economic realities of each country.
CARICOM Multi-Agency Health and Family Life Education Project
Keywords: health and family life education; HFLE; needs assessment